Thermodynamic parameters of adsorption of 1,10-phenanthroline and 2,2′-bipyridyl on hematite, kaolinite and montmorillonites - Ferreiro, Eladio Avelino (2007)
The thermodynamic equilibrium constant (K), free energy (ΔG), enthalpy (ΔH), entropy (ΔS), isosteric heat (qst) of adsorption, and the constant (kL) of the Langmuir adsorption equation using the adsorption isotherms (pH 6) of 1,10-phenanthroline (OP) and 2,2′-bipyridyl (BP) on hematite, sodium kaolinite (Na-K), sodium montmorillonite (Na-Mt) and hydroxy-aluminium montmorillonite (HAM) were obtained. The magnitude of enthalpy and isosteric heat established that adsorption on these minerals is a physical phenomenon. The equilibrium reaction constant (K) was used to calculate the enthalpy (ΔH) and free energy (ΔG) for OP adsorption, parameters which could not be obtained by applying the constant (kL) of the Langmuir equation of adsorption. The isosteric heat for hematite, Na-K, Na-Mt and HAM in kJ mol-1 was: 10.8-0.66, 13.4-28.6, 9.12-16.0 and 13.5-6.35, respectively. The equilibrium reaction constant (K) was similarly used to obtain the enthalpy (ΔH) and free energy (ΔG) for BP adsorption on hematite, Na-K and Na-Mt, but this was not possible in the case of HAM. The kL constant did not behave as K in the adsorption of BP; it was only possible to obtain ΔG with values close to the order of magnitude of those obtained with K, but not ΔH. Isosteric heat in kJ mol-1 was -28.2 to -17.1 for hematite, 0.388-7.43 for Na-K, 3.55-7.47 for Na-Mt, and -0.363 to 2.30 for HAM. The adsorption of OP on hematite, Na-K, Na-Mt and HAM is an exothermic process, as is BP adsorption on Na-K and Na-Mt. BP adsorption on HAM, however, is endothermic at low surface cover and exothermic at a surface cover greater than 0.5 mol kg-1. The negative ΔS values obtained for both systems of adsorption are likely due to the displacement of solvent molecules on the surface by OP and BP solutes. In the case of OP adsorption hematite presents a heterogeneous surface and the other minerals a homogeneous surface. In the case of BP, all the minerals present heterogeneous surfaces.